Predictive value of Leukocyte ImmunoTest (LIT™) in cancer patients: a prospective cohort study - Li, Xiaomeng; Ma, Xiaojun; Liu, Yifeng; Chang, Enqiang; Cui, Jiang; Ma, Daqing; Zhang, Jiaqiang (Frontiers in Oncology, 2022)
Early diagnosis of cancer is crucial to initiate prompt treatment for better patients’ outcomes. The host immune function and its associated modulators are considered to be potential biomarkers for early cancer diagnosis. Immune and immune-checkpoint biomarkers have been reported to contribute to cancer development whilst a high neutrophil-to-lymphocyte ratio has been shown to be associated with poor survival outcomes in a variety of cancers. One hundred and sixty-one cancer patients were recruited to take a cost-effective novel Leukocyte ImmuneTest (LIT). LIT was measured to objectively determine the pre-treatment immune status of patients. The correlation between LIT and other conventional diagnostic markers or tumour-related variables were then investigated. Significant correlation between LIT and white blood cell count, smoking status and tumour stage 4 were found. In addition, LIT score significantly differentiated between malignant and benign tumors in this study population. Our work raises the possibility to use LIT for general screening surveillance before further costly specialised equipment to be applied for cancer diagnosis.